2023
DOI: 10.1002/smtd.202301451
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Use Self‐Assembled Monolayer Controlling Charge Carrier Extraction in Organic Solar Cells

Zhuo Xu,
Rico Meitzner,
Aman Anand
et al.

Abstract: The development and use of interface materials are essential to the continued advancement of organic solar cells (OSCs) performance. Self‐assembled monolayer (SAM) materials have drawn attention because of their simple structure and affordable price. Due to their unique properties, they may be used in inverted devices as a modification layer for modifying ZnO or as a hole transport layer (HTL) in place of typical poly(3,4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) in conventional devices. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…This could significantly suppress photo-oxidation at the ZnO/active layer interfaces, enhancing device stability and PCE of the i-OSCs. , Furthermore, atomic force microscopy (AFM) studies revealed root-mean-square (RMS) roughness values of 2.24, 1.54, and 1.58 nm for the pristine, ODT-treated, and OTMS-treated ZnO films, respectively, suggesting a smoother surface morphology for SAM-modified ZnO films compared to the pristine film (see Figure S1). These findings suggest successful coverage of the ZnO surface by an ultrathin layer formed by the thiolate and silane ligands, which significantly reduced the surface roughness as evidenced by the AFM results …”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…This could significantly suppress photo-oxidation at the ZnO/active layer interfaces, enhancing device stability and PCE of the i-OSCs. , Furthermore, atomic force microscopy (AFM) studies revealed root-mean-square (RMS) roughness values of 2.24, 1.54, and 1.58 nm for the pristine, ODT-treated, and OTMS-treated ZnO films, respectively, suggesting a smoother surface morphology for SAM-modified ZnO films compared to the pristine film (see Figure S1). These findings suggest successful coverage of the ZnO surface by an ultrathin layer formed by the thiolate and silane ligands, which significantly reduced the surface roughness as evidenced by the AFM results …”
Section: Resultsmentioning
confidence: 69%
“…17,18 Recently, self-assembled monolayers (SAMs) have emerged as a promising strategy for modifying metal and metal oxide surfaces in OSCs. 19,20 The main effect caused by applying SAMs to metal-oxide surfaces is the formation of interfacial dipoles, which can assist with electron extraction and enhance performance. SAMs have been successfully employed as interface modifiers between the metal oxide and active layers in OSC devices, achieving a record PCE of 18.4% 21 and an extrapolated lifetime of 20 years.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic solar cells (OSCs) have garnered considerable attention due to their merits including being flexible, lightweight, and solution-processable for manufacturing. Recently, the maximum power conversion efficiency (PCE) of single-junction OSCs has approached nearly 20%, which is attributed to the emergence of nonfullerene photovoltaic materials together with the continuous optimization of device engineering. A typical OSC is structured by two electrodes sandwiching a photoactive layer with hole (HTL) and electron (ETL) transport layers between their interfaces, in which the photoactive layer determines light-harvesting and free-carrier production, while the HTL/ETL play a vital role in carrier transport and long-term operational stability. …”
Section: Introductionmentioning
confidence: 99%